2007
DOI: 10.1161/circulationaha.106.663807
|View full text |Cite
|
Sign up to set email alerts
|

Annual Rate of Transvenous Defibrillation Lead Defects in Implantable Cardioverter-Defibrillators Over a Period of >10 Years

Abstract: Background— The number of patients with longer follow-up after implantation of an implantable cardioverter-defibrillator is increasing continuously. Defibrillation lead failure is a typical long-term complication. Therefore, the long-term reliability of implantable cardioverter-defibrillator leads has become an increasing concern. The aim of the present study was to assess the annual rate of transvenous defibrillation lead defects related to follow-up time after lead implantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
380
5
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(409 citation statements)
references
References 26 publications
8
380
5
9
Order By: Relevance
“…However, patients may already be at risk for SCD during initiation and optimization of heart failure medication. On the other hand, too early ICD implantation exposes the patient to the risk of early and late complications 18, 19. A substudy of the MADIT‐II trial showed a greater benefit of primary preventive ICD implantation after remote MI 20.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients may already be at risk for SCD during initiation and optimization of heart failure medication. On the other hand, too early ICD implantation exposes the patient to the risk of early and late complications 18, 19. A substudy of the MADIT‐II trial showed a greater benefit of primary preventive ICD implantation after remote MI 20.…”
Section: Discussionmentioning
confidence: 99%
“…A percentage of transvenous system malfunctions is attributable to lead‐related problems and may require additional intervention 5. The transvenous ICD lead has been called the “weakest” link in ICD therapy and the most frequent source of serious complications associated with ICDs 6, 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Also lead longevity is a major concern in the long term: Kleemann et al reported that only 60% of leads functioned properly after an eight-year follow-up. 20 Secondly, most patients are not aware of an imminent risk of sudden death when offered ICD therapy, and labelling them as such may profoundly influence the quality of life. It is therefore not surprising that up to 38% of ICD recipients experience symptoms that meet criteria for anxiety disorders, with younger patients and those receiving multiple shocks at greater risk.…”
Section: Limitations Of Current Guidelinesmentioning
confidence: 99%